Review of pollutants in urban road dust and stormwater runoff: part 1. Heavy metals released from vehicles. Issue 3 (1st September 2016) - Hwang, Hyun-Min; Fiala, Matthew J.; Park, Dongjoo; Wade, Terry L.
ABSTRACT: Urban road dust can be highly enriched with trace metals such as copper, lead, zinc, and platinum group elements (PGEs) that are released primarily from vehicles. Concentrations of these metals are up to about 100 times higher than background levels. Lead concentrations in sediment core have declined dramatically due to phase out of leaded gasoline. Recent ban on the use of lead wheel balancing weight in Europe and in some US states will accelerate the decline of lead in the environment. Concentrations of copper, zinc, and PGEs in sediments in many urban areas have increased continuously due to increase of urban sprawl and increased numbers and travel distance of vehicle. Wear of brake pads and tyres are the primary sources of copper and zinc in urban road dust. PGEs have been released from catalytic converters since the mid-1970s. Contaminated urban road dust is picked up by stormwater runoff and delivered into local receiving waterbodies (e.g. streams, rivers, lakes, and estuaries). Concentrations of these metals in waterbodies and sediments receiving stormwater runoff from densely populated urban areas are high enough to impair the health of aquatic organisms and frequently exceed water quality criteria and sediment quality guidelines. In order to improve the quality of urban waterbodies, legal regulations are necessary to reduce release of toxic metals from vehicle use as demonstrated in the case of lead in gasoline. Recent regulations and agreement to reduce copper content in brake pads to 0.5% by 2026 in the USA should result in significant reduction of copper entering urban watersheds. A less optimal option is removal of suspended sediments from stormwater runoff before they enter receiving waterbodies using best management practices such as retention ponds, detention basins, and grass swales.